Effect of mismatched place-of-stimulation on binaural fusion and lateralization in bilateral cochlear-implant users - Kan, Alan; Stoelb, Corey; Litovsky, Ruth Y.; Goupell, Matthew J. (The Journal of the Acoustical Society of America, 2013)
Bilateral cochlear implants (CIs) have provided some success in improving spatial hearing abilities to patients, but with large variability in performance. One reason for the variability is that there may be a mismatch in the place-of-stimulation arising from electrode arrays being inserted at different depths in each cochlea. Goupell et al. [(2013b). J. Acoust. Soc. Am. 133(4), 2272–2287] showed that increasing interaural mismatch led to non-fused auditory images and poor lateralization of interaural time differences in normal hearing subjects listening to a vocoder. However, a greater bandwidth of activation helped mitigate these effects. In the present study, the same experiments were conducted in post-lingually deafened bilateral CI users with deliberate and controlled interaural mismatch of single electrode pairs. Results show that lateralization was still possible with up to 3 mm of interaural mismatch, even when off-center, or multiple, auditory images were perceived. However, mismatched inputs are not ideal since it leads to a distorted auditory spatial map. Comparison of CI and normal hearing listeners showed that the CI data were best modeled by a vocoder using Gaussian-pulsed tones with 1.5 mm bandwidth. These results suggest that interaural matching of electrodes is important for binaural cues to be maximally effective.